2005
DOI: 10.1115/1.1811090
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Augmentation of Internal Convection Over Pins in Staggered-Pin Fin Arrays

Abstract: The objective of this research was to investigate pin fin midline heat transfer in terms of our understanding of stagnation region heat transfer for cylinders in cross flow and turbine airfoils. An experimental investigation was conducted in a staggered-pin fin array at Reynolds numbers of 3000, 10,000, and 30,000 based on the maximum velocity between cylinders. Midline distributions of static pressure and heat transfer were acquired for rows 1 through 8 at the three Reynolds numbers. Turbulence measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Chyu et al [1998a] predicts 10% to 20% lower heat transfer over the present testing range. The results from Ames et al [2004] are similar to Chyu et al [1998a] geometry is similar to the predictions given by Zukauskas [1972], and Chyu et al [1998a].…”
Section: Reynolds Number Effectssupporting
confidence: 78%
See 2 more Smart Citations
“…Chyu et al [1998a] predicts 10% to 20% lower heat transfer over the present testing range. The results from Ames et al [2004] are similar to Chyu et al [1998a] geometry is similar to the predictions given by Zukauskas [1972], and Chyu et al [1998a].…”
Section: Reynolds Number Effectssupporting
confidence: 78%
“…Both Ames et al [2004] andChyu et al [1998a] give lower results. The combined pin and endwall heat transfer result shown in Table 5-2 from my study agrees well with Metzger et al [1982a].…”
Section: Heat Transfer From a Single Row Of Pin Finsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Reynolds number dependency is unclear for Metzger and Haley [1982b] and Ames et al [2004]. Both only presented three data points across the Reynolds number range.…”
Section: Reynolds Number Effectsmentioning
confidence: 99%
“…are crucial parameters in determining the heat transfer and friction factor. Ames et al [6] studied the local Nusselt number and turbulent flow structure characteristics in a pin fin channel and their study revealed that the unsteadiness in the wakes, the shear layers formed between the wake and the high speed main stream flow. Sara [7] presented the characteristics of heat transfer and friction and analyzed the convective heat transfer through a rectangular channel with pin fins of square cross sectional and attached over a flat surface; the pin fins were arranged in a staggered manner, with varied clearance ratios C/H.…”
Section: Introductionmentioning
confidence: 99%